Fabrication and Characterization of PCL/Chitosan and PCL/AgNPs Electrospun Nanofibers for Surface Modification of Cotton Textile - Angela Quiroga-Vergel; Dianney Clavijo-Grimaldo; Ana M. Muñoz-Gonzalez; Nubia Ponce-Zapata; Ciro Casadiego-Torrado (Chemical Engineering Transactions)
In the textile industry, particularly for hospital applications, ensuring optimal mechanical properties, balanced hydrophilicity/hydrophobicity, and infection resistance is essential to prevent cross-contamination. Nanofibers offer a promising solution due to their biocompatibility, high surface-to-volume ratio, porosity, tensile strength, and functionalization potential for added properties like antimicrobial. This study electrospinning was used in the fabrication of polycaprolactone/chitosan (PCL/CHT) and polycaprolactone/silver nanoparticles (PCL/AgNPs) nano/microfibers, applied to commercial cotton fabric. Characterization via scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), confirming the presence of nano/microfibers in cotton, while tensile tests showed improved fabric strength with binder pre-treatment, maintained after coating. The finished textiles exhibited hydrophobic properties, as evidenced by contact angle measurements. Microbiological tests with both gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus) bacteria, demonstrated that AgNPs effectively inhibited bacterial growth. The antibacterial properties of PCL/CHT were lower than those of PCL/AgNPs but like those reported in the literature. These findings highlight the potential of nano/microfibers in advanced healthcare textiles.